2011
DOI: 10.1596/1813-9450-5691
|View full text |Cite
|
Sign up to set email alerts
|

Exports and International Logistics

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
(38 reference statements)
2
11
0
Order By: Relevance
“…The LPI of importing countries has a positive significant impact on the export volume of foreign exporters. These results are consistent with previous studies [4,5,[33][34][35]. In addition, the LPI coefficient of exporting countries is higher than that of importing countries, indicating that the impact of LPI on the international trade of exporting countries is bigger than that for importing countries.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The LPI of importing countries has a positive significant impact on the export volume of foreign exporters. These results are consistent with previous studies [4,5,[33][34][35]. In addition, the LPI coefficient of exporting countries is higher than that of importing countries, indicating that the impact of LPI on the international trade of exporting countries is bigger than that for importing countries.…”
Section: Resultssupporting
confidence: 92%
“…Behar and Manner [33] analyzed the relationship between the logistics performance of importing, exporting countries, and bilateral exports. They found that the logistics performance of exporting countries has a significant positive impact on export volume.…”
Section: Logistics Performance and International Tradementioning
confidence: 99%
“…This is a positive function ofp and an estimate of the latent variable Z ij . As Behar et al (2009a) explain, attaching a Pareto distribution to rm productivity maps to a consistent estimate of the number of rms protable enough to invest abroad. The second stage includes controls for rm selection ln(e δẑij − 1) and country selection ( η ij ).…”
Section: Appendix: Implementing the Gravity Model With Firm Heterogmentioning
confidence: 99%
“…Third, we follow Freund and Rocha (2010) and restrict exports to new products to deal with reverse causality of exports to trade facilitation, as trade in new goods cannot affect investment in 'hard infrastructure' or institutional reform. To take into account omitted multilateral resistance effects, we follow the procedure originally proposed by Baier and Bergstrand (2009) for one-stage gravity estimates, and extended by Behar et al (2009) to a twostage sample selection model, which consists of correcting bilateral variables. Our results suggest that trade facilitation reforms could improve the export performance of developing countries at the extensive and intensive margin, especially investment in physical infrastructure and regulatory reform to improve the business environment.…”
Section: Introductionmentioning
confidence: 99%